INFLUENCE OF WEATHER ON THE PROGRESS OF CORYNESPORA LEAF SPOT IN COTTON (Journal of Plant Disease Sciences, 2025)
Corynespora leaf spot in three BG II cotton hybrids: Aadhya, Akira, and US 7067. Disease severity was recorded weekly from the first appearance of symptoms through to the boll bursting and picking stage, using a 0 to 4 scale on twenty randomly tagged plants per plot.Concurrently, daily weather data—including maximum and minimum temperatures, morning and evening relative humidity, rainfall, number of rainy days, sunshine hours, wind speed, and evaporation—were recorded from the meteorological observatory. Correlation and multiple regression analyses were performed between percent disease index (PDI) and weather parameters using MS Excel.Results revealed that morning relative humidity and sunshine hours showed a significant positive correlation with PDI. In contrast, maximum and minimum temperatures, number of rainy days, and wind speed had significant negative correlations. Multiple regression analysis identified minimum temperature, evening relative humidity (RH II), and rainfall as common factors that significantly influenced the disease progress across all three cotton hybrids.
Keywords: Cotton; Corynespora leaf spot; Phonological stage; Weather parameters